HUBUNGAN DUKUNGAN KELUARGA (SUAMI) DENGAN PEMBERIAN ASI EKLUSIF DI WILAYAH PERKOTAAN DAN PEDESAAN : SCOPING REVIEW: The Relationship Between Family Support (Husband) and Exclusive Breastfeeding in Urban and Rural Areas: A Scoping Review - Guterres, Dulce Maria; Mufdlilah; Ismarwati (LPPM - STIKES Pemkab Jombang, 2025)
Exclusive breastfeeding for the first six months of a baby's life is the main recommendation of WHO to support optimal infant growth and maternal-child health. However, the success rate still varies, especially between urban and rural areas. One of the main factors influencing the success of exclusive breastfeeding is the husband's support in the form of emotional, informational, and practical support. Research shows that mothers who receive active support from their husbands are more likely to succeed in exclusive breastfeeding. Social, economic, and cultural differences influence the pattern of this support across regions. In addition, factors such as education level, maternal employment status, and cultural norms contribute to the low prevalence of exclusive breastfeeding in developing countries. Mothers who work in the formal sector face greater challenges in maintaining exclusive breastfeeding due to limited maternity leave and lactation facilities. Therefore, the involvement of husbands is not only important in supporting mothers at home, but also in policy advocacy at the workplace. This study aims to analyze the role of husbands in supporting the success of exclusive breastfeeding and the differences in support between urban and rural areas. The results of the study are expected to be the basis for health policies and family-based education programs to increase the success rate of exclusive breastfeeding.